Maringá’s Zone 10 as a memory space: abandoned industrial urban areas - Cardoso, Carolina Fressatti; Vernice, Rilton Robson Lima; Wedekin, Gabriela Oliveira; Motta, Mariana Medeiros da (Revista Nacional de Gerenciamento de Cidades, 2022)
Currently, it has become frequent to find urban voids generated by former industrial spaces that have fallen into disuse in the urban fabric. Industrial ruins, although part of the cultural and historical imaginary of a society, are usually found in abandoned, decharacterized or destroyed situations, sometimes creating hostile environments. Hence, memory, once intimately linked to the development of the city, is slowly being forgotten, consumed by time. Zone 10, located in Maringá-PR, presents such characteristics: historically marked by an industrial complex of relevance for the construction and industrial development of the city and the Northern region of Paraná, it was later abandoned by the industries, and it became one of the biggest urban voids surrounding the city center, deteriorating over the years and leading to a feeling of insecurity in its vicinity. The objective of this article is to debate such a subject through the theories and concepts of urban recovery of industrial areas, seeking to highlight the potentiality of its preservation in projects that seek to revitalize and revive these urban voids, as well as transposing the discussion to the specific object of study, pointing out the relevance of Zone 10 as a heritage of the collective industrial memory of the city of Maringá, and the importance of its preservation in future urban projects. Based on bibliographic analysis, we sought to approximate literature with information gathered about the area, highlighting the importance of its preservation for the maintenance of that space and the city’s memory.